Analisis Tingkat Perkembangan Kawasan Agropolitan Desa Perpat Kabupaten Belitung Berbasis Komoditas Unggulan Ternak Sapi Potong - Suyitman Suyitman; S.H. Sutjahjo (Universitas Andalas, 2011)
This study aims to analyze the level of area development of Perpat Agropolitan Village - District of Belitung-Province of Bangka Belitung based on beef cattle commodity in terms of 5 (five) dimensions agropolitan level of area development, namely: the dimensions of agribusiness, agro-industry, marketing, infrastructure and superstructure. This study use a method of analysis of Multidimensional Scaling (MDS) called Rap-agrop and the results are expressed in index form and the status of sustainability. The result of MDS analysis shows the level of development area of Perpat agropolitan village, based on beef cattle farm commodities, was still low, ie: including Pre Regions Agropolitan. This region has an index value of Rap-agrop dimensional good enough for agribusiness (50.57%), infrastructure (64.49%), and the superstructure (57.23%), while the dimensions of agro-industries (6.52%) and marketing (9.98%) had an index value that is poorly. The key factors that strongly affected the level of development of the region agropolitan Perpat-Belitung, namely: 1) the production of beef cattle and 2) the production of processed meat. To enhance the development of this area is to do a thorough improvement of all attributes that are sensitive, so that all dimensions in the region agropolitan Perpat become enhanced and more sustainable.